Different Functions of Recombinantly Expressed Domains of Tenascin-C in Glial Scar Formation - Bijelić, Dunja; Adžić, Marija; Perić, Mina; Jakovčevski, Igor; Förster, Eckart; Schachner, Melitta; Andjus, Pavle R. (Frontiers in Immunology, 2021)
Extracellular matrix glycoprotein tenascin-C (TnC) is highly expressed in vertebrates during embryonic development and thereafter transiently in tissue niches undergoing extensive remodeling during regeneration after injury. TnC’s different functions can be attributed to its multimodular structure represented by distinct domains and alternatively spliced isoforms. Upon central nervous system injury, TnC is upregulated and secreted into the extracellular matrix mainly by astrocytes. The goal of the present study was to elucidate the role of different TnC domains in events that take place after spinal cord injury (SCI). Astrocyte cultures prepared from TnC-deficient (TnC-/-) and wild-type (TnC+/+) mice were scratched and treated with different recombinantly generated TnC fragments. Gap closure, cell proliferation and expression of GFAP and cytokines were determined in these cultures. Gap closure in vitro was found to be delayed by TnC fragments, an effect mainly mediated by decreasing proliferation of astrocytes. The most potent effects were observed with fragments FnD, FnA and their combination. TnC-/- astrocyte cultures exhibited higher GFAP protein and mRNA expression levels, regardless of the type of fragment used for treatment. Application of TnC fragments induced also pro-inflammatory cytokine production by astrocytes in vitro. In vivo, however, the addition of FnD or Fn(D+A) led to a difference between the two genotypes, with higher levels of GFAP expression in TnC+/+ mice. FnD treatment of injured TnC-/- mice increased the density of activated microglia/macrophages in the injury region, while overall cell proliferation in the injury site was not affected. We suggest that altogether these results may explain how the reaction of astrocytes is delayed while their localization is restricted to the border of the injury site to allow microglia/macrophages to form a lesion core during the first stages of glial scar formation, as mediated by TnC and, in particular, the alternatively spliced FnD domain.